2022
DOI: 10.3390/ijerph192013317
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Esteem in the Academic Performance of Rural Students in China

Abstract: The self-esteem of students may be significantly associated with their academic performance. However, past research in developing contexts on this issue is limited, particularly among early adolescents. Using a sample of 3101 students from rural primary and junior high schools in China, this study measured their self-esteem by the Rosenberg Self-Esteem Scale (RSES) and explored its association with academic performance. Our findings indicate that students in rural China had both significantly lower self-esteem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
1
7
2
Order By: Relevance
“…Another finding in the present study was that there was no correlation between self-esteem and academic performance; this was in contrast with a study done in China which found a positive correlation between self-esteem and academic performance [25]. Interestingly, the current study found that self-esteem was generally higher in academic year students than clinical year students.…”
Section: Discussioncontrasting
confidence: 99%
“…Another finding in the present study was that there was no correlation between self-esteem and academic performance; this was in contrast with a study done in China which found a positive correlation between self-esteem and academic performance [25]. Interestingly, the current study found that self-esteem was generally higher in academic year students than clinical year students.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the selfesteem of RLBC, this study revealed no signi cant gender differences. This is consistent with other surveys of the self-esteem of RLBC in different Chinese provinces 40,41,42 . Similarly, other studies also found that gender did not strongly in uence of self-esteem, including children in the U.S. and Germany 43,44 .…”
Section: Discussionsupporting
confidence: 92%
“…This nding contradicts the ndings of another study conducted in Turkey showing that an increase in parents' education level is associated with an increased self-esteem among adolescents [33]. Another study in China showed that adolescents whose fathers had more than nine years of education were 6.7% less likely to have low self-esteem [34].…”
Section: Discussioncontrasting
confidence: 66%
“…The study showed that 94.5% of adolescents in high school reported poor self-esteem. Academic stress [31] and academic success [32] are associated with (and can affect) self-esteem among adolescents. Since high school is a period of preparing for the university admission test in Afghanistan, academic pressure resulting from this could have led to high school students reporting lower self-esteem.…”
Section: Discussionmentioning
confidence: 99%